Association between Delay to Radical Prostatectomy and Clinically Meaningful Outcomes among Patients with Intermediate and High-Risk Localized Prostate Cancer. Issue 3 (25th March 2022) - Lee, Maggie C.; Erickson, Tyler R.; Stock, Shannon; Howard, Lauren E.; De Hoedt, Amanda M.; Amling, Christopher L.; Aronson, William J.; Cooperberg, Matthew R.; Kane, Christopher J.; Terris, Martha K.; Klaassen, Zachary; Freedland, Stephen J.; et al.
Abstract : Purpose: There are limited data regarding the effect of treatment delays on important long-term outcomes among men with intermediate/high-risk prostate cancer (PC). Materials and Methods: We identified 3, 962 men with intermediate/high-risk disease from the SEARCH cohort treated with radical prostatectomy (RP) from 1988 to 2018. Cox proportional hazard models assessed the association between time from biopsy to RP (up to 1 year) and time to castration-resistant PC (CRPC), metastasis and all-cause mortality. Interaction terms were used to test for effect modification by risk group. Results: Of the 3, 962 men, 167 developed CRPC, 248 developed metastases and 884 died after a median followup of 85 months. Longer delays between biopsy and RP were associated with a decreased risk of CRPC (adjusted HR=0.88, 95% CI: 0.80–0.98, p=0.02), independent of D'Amico risk group (interaction p >0.05). In men with intermediate and high-risk disease, we found no statistically significant association between length of time to RP and risk of developing metastases (p=0.5 and 0.9, respectively) or all-cause mortality (p=0.1 and 0.1, respectively). Conclusions: Among men with intermediate and high-risk PC, we found no statistically significant increased risk of adverse long-term outcomes, including CRPC, metastasis and death, for men who had treatment delays up to 1 year following PC diagnosis.